Students’ Problems in Completing Sentence by Using Linking Be at First Grade of SMPN 1 Kerinci - Efa Silfia (Universitas Batanghari Jambi, 2019)
One of the rules of grammar carries out important rule that is using simple linking be. Linking Be shows existence or, as the case may be, nonexistence. This research was aimed to find out the students’ problems in completing sentence by using linking be at first grade of SMPN 1 Kerinci Academic Years 2018/2019 and the causes of the students’ problems in completing sentence by using linking be at first grade of SMPN 1 Kerinci Academic Years 2018/2019. The design of this research was descriptive research. The population was at the grade VII students of SMPN 1 Kerinci. There were 156 students which consisted of 7 classes as the population. This population was tested by using Bartlett test to make homogeneity. Then, the sample was VII B. The instruments were given grammar test in multiple choices as quantitative data and took interview as qualitative data. Moreover, it was also proven by the result of the total percentage of the students. There were 47% students who got very good, 26% students got good, 21.7% students got fair, 4.3% got weak and no student got poor And mean score of the students was 75.6. Based on interview to students, there were some problems faced by the students’ in completing sentence by using linking be. They only made mistake in some cases. But they have learned and known which one to be is when they were asked to make sentence. Based on the result of data analysis, it was concluded that generally the students’ students’ problems in completing sentence by using linking be at first grade of SMPN 1 Kerinci was good.